Teaching English as a foreign language - Geoffrey Broughton (London ; New York Routledge, 1980)
For the many categories of EFL teachers throughout the world, this book aims to examine the main principles which concern them. By drawing upon their experience the authors have indicated a modern and practical approach.
Keywords: English language -- Study and teaching -- Foreign speakers; Foreign language study -- English as a Second Language; Non-English speaking students -- Education -- Curriculum subjects -- English language -- Teaching